PURWARUPA LOGIG ANALYZER BERBASIS LABVIEW MENGGUNAKAN ARDUINO UNO - , FEBRIANI HUSNIAH; , R. Sumiharto, S.Si., M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
designed to facilitate the use of logic analyzer needs shown on LabVIEW. This system consists of a arduino uno and LabVIEW. Logic analyzer prototype is designed using LabVIEW software and data acquisition using the arduino uno. Done in the LabVIEW control and readout signal input. Serial communication between arduino uno with LabVIEW using USB cable. Data acquisition process through analog pin Arduino Uno is pin A0 to A5. Input is obtained from a function generator to a channel and the system is able to process a maximum six channels. Logic analyzer prototype is able to display signals having a frequency of 5 Hz to 100Hz. The signal acquisition speed is set at 500 Hz and a sample set of 50. The system will display the signal in the period 0 to 0.1 s per sample. This system is more suitable if it is used to display the frequency of the function generator, rather than as a series of decoder circuit because the decoder circuit requires the same period.